Understanding The Components of Curriculum: Aims, Goals, and Objectives - Thoip Nasution, Putra; Malik, Fachrizha (CV Edu Tech Jaya, 2025)
The understanding of the components of a curriculum is essential in the design and implementation of an educational program. Aims, goals, and objectives are three fundamental elements that work together to guide the learning experiences of students and ensure that they are able to achieve the desired outcomes. Aims refer to the overarching intentions of the curriculum, such as the values and beliefs that it seeks to promote. Goals are more specific, outlining the specific knowledge and skills that students should attain. Objectives are the most specific, outlining the specific learning outcomes that students should achieve in order to meet the goals of the curriculum. In this paper, we will delve into the significance of these three components and how they work together to create a comprehensive and effective curriculum.